Analisis Kesalahan Penulisan Fonologi Bahasa Jawa Pada Lirik Lagu Satru 2 Karya Denny Caknan - Nova Auliatul Azizah; Bagus Wahyu Setyawan (Estetik)
Language errors are often not realized by readers and song lyricists on Youtube. This is because not all media users understand the rules of writing Javanese language properly and correctly. This study aims to analyze errors in Javanese writing in the lyrics of The Satru 2 song by Denny Caknan on the Denny Caknan youtube account channel uploaded in February 2022.this study uses qualitative descriptive research methods. In this study, the data sources used came from primary and secondary data sources. The primary data source is the lyrics of the song Satru 2 by Denny Caknan on Denny Caknan's Youtube channel, while the source of the skunder data is in the form of documentation taken from various books, articles, and journals with similar discussions. In this study, it used a note-taking technique, namely by listening to Youtube by recording lyrics and errors in writing Javanese. The results of the study, it can be concluded that there was a phonological writing error in writing the lyrics of the song Satru 2 by Denny Caknan. There are five vowel words out of five sentences of incorrect writing, namely in the words wis, believe, what, trima, and work. Most javanese phonology on vowel phoneme errors that should be [a] written [o].